(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Once these epistemological approaches interact with the legal reasoning of the judge or interplay with the current patterns of organization featured by courts and legal institutions, the overall outcome is deeply and widely influenced by the degree of awareness actors enjoy with regard to 1) how to combine these different approaches, 2) how to make the best for the quality of justice out of this interplay 3) how to make for the laypeople and the society the use of sciences and technologies applied within the legal and justice sector. The author suggests a new model of professionalism for the XXI legal and justice sector, where different epistemological regimes enter into a virtuous dialogue.